(untitled) (GIST – Education and Learning Research Journal, 2021)
Direct instruction of Social Emotional Learning (SEL) has been suggested for improving academic performance and reducing behavioral issues in classrooms (CASEL, 2020). This exploratory study provides insight into how a group of Ecuadorian elementary school teachers define and understand SEL. It examined changes in teachers’ perspectives and beliefs about their role in SEL integration in elementary school classrooms, after a full-day workshop focused on SEL integration. Quantitative and qualitative data collected before, during and after the SEL workshop indicated a positive change in the teachers’ foundational knowledge of SEL after participation in the workshop; however, there was no observed change in the teachers’ perceptions of their role in the actual implementation of SEL. Challenges and future implications for an effective integration of SEL are discussed in this research article.